2008
DOI: 10.1089/jmf.2007.650
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate Juice and Extracts Provide Similar Levels of Plasma and Urinary Ellagitannin Metabolites in Human Subjects

Abstract: Pomegranate juice (PJ), a rich source of polyphenols including ellagitannins, has attracted much attention due to its reported health benefits. This has resulted in the consumption of liquid and powder pomegranate extracts as alternatives to PJ. Therefore establishing the bioavailability of polyphenols from these extract preparations is necessary. Sixteen healthy volunteers sequentially consumed, with a 1-week washout period between treatments, PJ (8 ounces, Wonderful fruit variety), a pomegranate polyphenol l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(114 citation statements)
references
References 15 publications
4
103
1
Order By: Relevance
“…This loss of the antiplasmodial activity of ellagic acid after oral administration found in our study is correlated with the limited bioavailability of ellagic acid reported after pomegranate juice ingestion (24). These results are thus not limited to the anti-Plasmodium activity of ellagic acid but could be transposed to potential chemopreventive, antioxidant, and anti-inflammatory bioactivities of ellagitannins as used by health food consumers (especially in the United States), who appreciate pomegranate juice because it is one of the richest sources of ellagic acid.…”
Section: Discussionsupporting
confidence: 88%
“…This loss of the antiplasmodial activity of ellagic acid after oral administration found in our study is correlated with the limited bioavailability of ellagic acid reported after pomegranate juice ingestion (24). These results are thus not limited to the anti-Plasmodium activity of ellagic acid but could be transposed to potential chemopreventive, antioxidant, and anti-inflammatory bioactivities of ellagitannins as used by health food consumers (especially in the United States), who appreciate pomegranate juice because it is one of the richest sources of ellagic acid.…”
Section: Discussionsupporting
confidence: 88%
“…It has been reported that the metabolites such as ellagic acid were poorly detected in human plasma after consumed lots of ETs-rich fruit juice [7]. In this study, when compared to the control plasma, there were no metabolites found in plasma at different time points.…”
Section: Metabolites In Plasmacontrasting
confidence: 55%
“…These studies have reported that the bioavailability of ETs is very low and rarely detected in plasma after normal consumption of ET-rich foods [5,6]. Only the metabolites, such as ellagic acid (EA), gallic acid (GA) and their metabolites, can be detected in vivo [7]. However, other ingredients in foods or extracts may affect the metabolic process of ETs when they were taken simultaneously, and the metabolism of purified ETs is not reported.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the extracts from both organic and conventional V. labrusca leaves, which is the main species used in America to produce wines and grape juices (Seeram et al 2008), were tested in heart, liver and kidney tissues of rats. It was observed that both extracts were able to reduce the lipid and protein H 2 O 2 -induced damage in all tissues (Fig.…”
Section: Resultsmentioning
confidence: 99%